Are Nuclear Star Clusters the Precursors of Massive Black Holes? - Nadine Neumayer; C. Jakob Walcher (Advances in Astronomy)
We present new upper limits for black hole masses in extremely late type spiral galaxies. We confirm that this class of galaxies has black holes with masses less than 106M⊙, if any. We also derive new upper limits for nuclear star cluster masses in massive galaxies with previously determined black hole masses. We use the newly derived upper limits and a literature compilation to study the low mass end of the global-to-nucleus relations. We find the following. (1) The MBH-σ relation cannot flatten at low masses, but may steepen. (2) The MBH-Mbulge relation may well flatten in contrast. (3) The MBH-Sersic n relation is able to account for the large scatter in black hole masses in low-mass disk galaxies. Outliers in the MBH-Sersic n relation seem to be dwarf elliptical galaxies. When plotting MBH versus MNC we find three different regimes: (a) nuclear cluster dominated nuclei, (b) a transition region, and (c) black hole-dominated nuclei. This is consistent with the picture, in which black holes form inside nuclear clusters with a very low-mass fraction. They subsequently grow much faster than the nuclear cluster, destroying it when the ratio MBH/MNC grows above 100. Nuclear star clusters may thus be the precursors of massive black holes in galaxy nuclei.